Multimedia educativa de apoyo en el proceso para la enseñanza-aprendizaje de la asignatura de ciencias sociales del cuarto año de educación general básica para los (as) niños (as) de la escuela fiscal mixta 9 de Octubre de la parroquia San Pedro de Vilcabamba, período 2012-2013 - Ochoa Villa, Pedro Enrique (2014)
The development of this research work aims to develop a MULTIMEDIA EDUCATIVA DE APOYO EN EL PROCESO PARA LA ENSEÑANZA-APRENDIZAJE DE LA ASIGNATURA DE CIENCIAS SOCIALES DEL CUARTO AÑO DE EDUCACIÓN GENERAL BÁSICA PARA LOS (AS) NIÑOS (AS) DE LA ESCUELA FISCAL MIXTA “9 DE OCTUBRE” DE LA PARROQUIA SAN PEDRO DE VILCABAMBA, PERÍODO 2012-2013, the same that was developed to meet the prerequisite to obtain the degree of Bachelor of Computer Education, in compliance with established standards for graduation at the National University of Loja. In the present investigation the overall objective raised was: Develop educational multimedia support in the process of teaching and learning of the subject of Social Sciences of the fourth year of Basic General Education children (as) the Escuela Fiscal Mixta “Nueve de Octubre” in the parish San Pedro de Vilcabamba, in order to help acquire significant learning dynamically using modern tools that provides information technology in education today. The methods used in the development of this research work were: Scientist, Deductive and Inductive-Statistical Model, which allowed obtaining the theoretical information and discussion of the variables. Observation instruments were used to obtain real information on the characteristics of the place where the research work was developed, survey of the children of the school in question in order to identify needs to improve learning in Social Sciences and the interview which provided teachers with ideas and knowledge to the project. After analyzing the results it is concluded that as a solution to the problem created educational multimedia serving 100% support in the process of teaching and learning of the subject of Social Sciences was developed, classes (as) children (as) received from its implementation are interactive by 82% thanks to the media and the information that has, as well as the installation manual, programmer and built considering images and simple language in order to use that they can be 100% easily and efficiently.